The Effect of Liquidity Ratio (CR) And Solvency Ratio (DER) on the Stock Price of Companies in the Transportation and Logistics Subsector on the Indonesian Stock Exchange (2022-2024), with Profitability Ratio (ROE) as a Mediating Variable - Fitri Amanda; Acep Komara (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study is intended to analyze the effect of Liquidity Ratio (Current Ratio) and Solvency Ratio (Debt to Equity Ratio) on Stock Price with Profitability Ratio (Return on Equity) as a mediating variable in companies in the Transportation and Logistics subsector listed on BEI. This research utilizes a quantitative approach with an associative causal type. The initial sample consisted of 60 annual observations, then after manual outlier checks, 43 observations remained suitable for processing. Secondary data were sourced from annual financial statement and closing stock prices and were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The findings indicate that CR exerts a positive and significant influence on both stock prices and ROE, whereas DER exhibits a positive and significant impact on stock prices but no significant influence on ROE. ROE itself does not significantly impact stock prices and therefore does not mediate the relationship between CR or DER and stock prices. Accordingly, the influence of liquidity and solvency on stock prices is direct rather than indirect through ROE. The structural model has excellent fit based on the model fit indicators, but the coefficient of determination and predictive relevance values for stock prices and ROE are relatively low, indicating that there are other factors beyond CR, DER, and ROE that affect these two variables. In general, these findings support the signaling theory that liquidity and capital structure information are stronger signals for investors than profitability information in stock price formation in Transportation and Logistics companies in Indonesia.